EFFECTS OF LEMURU OIL AND ZNSO4 SUPPLEMENTATION IN THE DIET CONSISTED OF CACAO POD SILAGE AND UREA ON ZINC ABSORPTION AND GROWTH OF CALVES - Hartati, E (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2008)
An experiment conducted to study the effect on Zinc, prostaglandin-E2 (PGE2) concentaration, alkaline phosphatase activities (APA) in the growth of bull calves fed cocoa pod silage diet supplemented with lemuru oil (LO) and ZnSO4. The animals were randomly assigned into three group of treatments, i.e.:supplementation of 0, 25, 50 and 75 mg kg -1 diet ZnSO4 and 0, 1.5 and 3% kg -1 diet LO. Basal diet consisted of cocoa pod silage and concentrate consists of wheat bran, cassava waste, soya bean meal in the ratio 1:3 which contained 70% Total Digestible Nitrient (TDN) and 16% CP as prescribed by NRC (1988). The diet was the supplemented with 1% urea. LO and ZnSO4 supplementation in the diet was significantly increased Zinc absorption (P<0.01) as well as increased PGE2 concretation (P<0.14) in the growth of bull calves. Relationship of the rate of apparent Zinc Absorption (Va, mg.d-1) with the rate Zinc intake (Va, mg.d-1), PGE2 concentration (mg.L-1) and Vi interaction for the level of 0, 1,5 and 3% LO supplementation were: Va (0) = -5.69 + 0.976 Vi + 1.98 PGE2 ? 0.0855 Vi PGE2; Va (1.5) = -2.6 + 0.962 Vi ? 14.3 PGE2 + 0.435 Vi PGE2 and Va (3) = -5.69 + 1.03 Vi - 0.394 PGE2 + 0.125 Vi PGE2. Level of LO supplementation was significantly linier increased (P<0.01) in serum of APA. Relationships of Zinc absorption with APA for the level of 0, 1.5 and 3% LO supplementation was significantly (P<0.01) increased by the following equations: APA (0) = 3.90569 ? 0.0204 Va; APA (1.5) = 3.61119 ? 0.0167 Va and APA (3) = 4.18421 ? 0.0199 Va. The average daily gain of the animals (ADG, kg) could by state as ADG = 0.603 + 0.00025 Zn + 0.00004 Zn2 + 0.113 LO ? 0.0275 LO2 + 0.00002 Zn LO ? 0.00001 Zn2 LO2 (R2 = 0.653; Sb = 0.0926). It can be concluded that supplementation of LO or ZnSO4 in the diet can increased Zinc absorption in the growth of bull calves with their average daily gain was higher at 1.5% LO and 75 mg ZnSO4 kg-1 diet than other levels. (Animal Production 10(1): 50-54 (2008) Key Words: Absorption, zinc, prostaglandin-E2, phosphatase alkaline, calves